Leading under the lens: the role of subjective norms in shaping leadership in Sabah’s Islamic School - Saidah Mohd Said; Mohd Khairuddin @Jerry Abdullah; Sabariah Sharif (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
This study investigates the influence of subjective norms on the leadership behaviors of principals in Islamic schools in Sabah, Malaysia. The primary aim is to elucidate how cultural and community expectations impact leadership dynamics within these distinctive educational settings. Adopting a qualitative research design, this study engaged in-depth interviews with five esteemed Islamic school principals, providing a comprehensive analysis of leadership practices in these institutions. The research findings indicate that leadership behavior is significantly shaped by multiple factors: the prevailing organizational culture, adherence to professional standards, and the implementation of best practices inspired by highperforming schools. Additionally, the alignment with religious and ethical principles, alongside community expectations, is pivotal in defining effective school management. These subjective norms are integral to formulating a leadership approach that aligns with both professional standards and communal values. The results underscore the necessity for leadership practices that are both culturally and contextually appropriate, thereby enhancing school performance and management quality. The alignment of leadership behavior with professional and community expectations fosters an environment conducive to academic excellence, ethical development, and community engagement. This study provides valuable insights and recommendations for policymakers, educators, and stakeholders, aimed at guiding the development of training programs, policy frameworks, and support mechanisms to advance leadership effectiveness in Islamic educational contexts.